2016
DOI: 10.1016/j.jsxm.2016.07.006
|View full text |Cite
|
Sign up to set email alerts
|

Effect of 5α-Reductase Inhibitors on Sexual Function: A Meta-Analysis and Systematic Review of Randomized Controlled Trials

Abstract: Introduction 5α-Reductase inhibitors (5ARIs) are widely used for the treatment of benign prostatic hyperplasia (BPH) and androgenetic alopecia (AGA). Aim To review all the available data on the effect of 5ARIs on sexual function and assess whether 5ARIs increase the risk of sexual dysfunction. Methods A systematic search of the literature was conducted using … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
53
0
5

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 68 publications
(59 citation statements)
references
References 82 publications
1
53
0
5
Order By: Relevance
“…Purported mechanisms for these effects include the decreased production of neurosteroids, which may regulate sexual desire and function, and impaired testosterone metabolism, leading to relative oestrogen excess . Large randomized controlled trials of men on 5‐alpha‐reductase inhibitors for benign prostatic hypertrophy have shown increased sexual dysfunction compared with placebo; however, similar association with male pattern hair loss was not statistically significant . Sexual side‐effects have been reported by 43·6% of men informed about these potential effects vs. 15·3% in the uninformed .…”
Section: Frequency Of Reported Side‐effects Of Finasteride Use In Wommentioning
confidence: 99%
“…Purported mechanisms for these effects include the decreased production of neurosteroids, which may regulate sexual desire and function, and impaired testosterone metabolism, leading to relative oestrogen excess . Large randomized controlled trials of men on 5‐alpha‐reductase inhibitors for benign prostatic hypertrophy have shown increased sexual dysfunction compared with placebo; however, similar association with male pattern hair loss was not statistically significant . Sexual side‐effects have been reported by 43·6% of men informed about these potential effects vs. 15·3% in the uninformed .…”
Section: Frequency Of Reported Side‐effects Of Finasteride Use In Wommentioning
confidence: 99%
“…High‐quality studies were found to report persistent sexual side‐effects more frequently in placebo groups versus treated individuals suggesting that sexual dysfunction is not a direct result of therapy . A literature review of studies prescribing 5αRIs for androgenetic AGA versus BPH revealed a significant association between sexual dysfunction adverse events in BPH patients but not among AGA patients . Some suggest age may be a confounding factor, as sexual dysfunction increases with age, and BPH generally affects older men and necessitates a higher dose of 5αRI .…”
Section: Introductionmentioning
confidence: 99%
“…5,10,12 A meta-analysis on the effects of 5a-reductase inhibitors found a significant pooled relative risk for sexual dysfunction in men with benign prostatic hyperplasia (2.56, 95% CI ¼ 1.48e4.42) but no significant increased risk in men with AGA (1.21, 95% CI ¼ 0.85e1.72). 13 Recently, a clinical study described the main symptoms of subjects with PFS, including loss of penis sensitivity, decreased ejaculatory force, low penile temperature, smaller ejaculatory volume, anhedonia, lack of mental concentration, and loss of muscle tone or mass. 4 In particular, an immunohistochemical study found increased levels of the androgen receptor (AR) in epithelial and stromal cells from the foreskin of eight men with PFS compared with healthy men.…”
Section: Introductionmentioning
confidence: 99%